From regime‐building to implementation: Harnessing the UN climate conferences to drive climate action. (13th August 2022) - Obergassel, Wolfgang; Bauer, Steffen; Hermwille, Lukas; Aykut, Stefan C.; Boran, Idil; Chan, Sander; Fraude, Carolin; Klein, Richard J. T.; Mar, Kathleen A.; Schroeder, Heike; Simeonova, Katia
Abstract: The gap between the internationally agreed climate objectives and tangible emissions reductions looms large. We explore how the supreme decision‐making body of the United Nations Framework Convention on Climate Change (UNFCCC), the Conference of the Parties (COP), could develop to promote more effective climate policy. We argue that promoting implementation of climate action could benefit from focusing more on individual sectoral systems, particularly for mitigation. We consider five key governance functions of international institutions to discuss how the COP and the sessions it convenes could advance implementation of the Paris Agreement: guidance and signal, rules and standards, transparency and accountability, means of implementation, and knowledge and learning. In addition, we consider the role of the COP and its sessions as mega‐events of global climate policy. We identify opportunities for promoting sectoral climate action across all five governance functions and for both the COP as a formal body and the COP sessions as conducive events. Harnessing these opportunities would require stronger involvement of national ministries in addition to the ministries of foreign affairs and environment that traditionally run the COP process, as well as stronger involvement of non‐Party stakeholders within formal COP processes. This article is categorized under: Policy and Governance > International Policy Framework Abstract : The UN climate conferences can drive implementation across five governance functions, using both their roles as formal decision‐making body and as mega‐events.